2015
DOI: 10.7819/rbgn.v17i56.1915
|View full text |Cite
|
Sign up to set email alerts
|

Empirical research on Innovation in Family Business: literature review and proposal of an integrative framework

Abstract: Objective -The objective of this paper is to present the results of a systematic literature review concerning empirical research about innovation in the Family Business (FB).Design/methodology/approach -A comprehensive literature review based on an in-depth analysis of 59 empirical studies was carried out. Findings -The revision presents an integrative framework, identifying main determinants and dimensions of innovation; and summarizes main research avenues and existing gaps, in order to guide future research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 119 publications
0
21
0
1
Order By: Relevance
“…The study provides empirical evidence of belief systems being part of the family strategy to implement a culture of innovation as being a value perceived by the employees. Thus, as the literature advocates, an alignment is noted with the interests of the family-member managers, which include commitment and values for the consolidation of the family business (Acquaah, 2013;Carlock & Ward, 2001;Chrisman, Chua & Kellermanns, 2009;Diehl, 2006;Miller et al 2007;Padilla et al, 2015).…”
Section: Analysis and Discussion Of The Interface Between The Use Of mentioning
confidence: 99%
See 1 more Smart Citation
“…The study provides empirical evidence of belief systems being part of the family strategy to implement a culture of innovation as being a value perceived by the employees. Thus, as the literature advocates, an alignment is noted with the interests of the family-member managers, which include commitment and values for the consolidation of the family business (Acquaah, 2013;Carlock & Ward, 2001;Chrisman, Chua & Kellermanns, 2009;Diehl, 2006;Miller et al 2007;Padilla et al, 2015).…”
Section: Analysis and Discussion Of The Interface Between The Use Of mentioning
confidence: 99%
“…Innovation (as a process or as a result) has been a recurrent theme in the studies on family and non-family businesses (Craig & Dibrel, 2006;Craig, Dibrell & Garret, 2014;Padilla-Meléndez, Dieguez-Soto & Garrido-Moreno, 2015). Patel and Chrisman (2014) found that family businesses are able to reconcile economic and non-economic objectives, investing in innovation in a more consistent way and with reduced risk, with the aim of increasing sales.…”
Section: Interface Between Msc and Strategymentioning
confidence: 99%
“…There is in the current literature of business and management sciences an extensive debate and discussion among researchers and scholars, about the concept of family firm and there is no consensus about a specific definition that satisfies everyone (Wortman, 1994;Upton and Heck, 1997;Upton et al, 2001). Furthermore, previous investigations published in the literature have attempted to identify the intrinsic qualities and the essential nature of family enterprises to incorporate them in a single definition but with no results (Padilla-Meléndez et al, 2015). Nonetheless, there seems to be a consensus among researchers and scholars that the essence of a family firms is a developed view for a by a coalition ruled and controlled by the members of one family, or by a small group of families who keep the ownership of the enterprise through the generations of the family or relatives (Chau et al, 1999).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Consequently, there are few investigations in the current literature of business and management sciences that analyze the dimensions or factors of innovation and its relation with business performance (Padilla-Meléndez et al, 2015). Due to the importance of this topic, the innovation and their relation with business performance within a context of family SMEs, this is a topic that must be widely analyzed and discussed by researchers, scholars and professionals in the field of marketing (Casillas and Acedo, 2007;Wright and Kellermanns, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Business cooperation is a widely discussed topic in the literature; however, few studies have focused on the specific case of the family businesses (FBs) and, moreover, there is no clear consensus on the relationship between cooperation and family character (Niemelä, 2004;Roessl, 2005;Pittino & Visintin, 2011;Classen, Van Gils, Bammens, & Carree, 2012;Franco & Haase, 2012;Pittino, Visintin, Bau', & Mazzurana, 2013;Alberti, Ferrario, Papa, & Pizzurno, 2014;Feranita, Kotlar, & De Massis, 2017). Given the importance of FBs around the world, and because their peculiarities make their strategic behavior different from that of other companies (Benito-Hernández, Priede-Bergamini, & López-Cózar-Navarro, 2014;De Massis, Frattini, Pizzurno, & Cassia, 2015;Padilla-Meléndez, Dieguez-Soto, & Garrido-Moreno, 2015), it seems relevant to develop an analysis in this research line (Feranita et al, 2017;Brinkerink, 2018).…”
Section: Introductionmentioning
confidence: 99%